2010
DOI: 10.1094/mpmi-23-6-0784
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobial Adaptation to Hosts, a New Facet in the Legume Root-Nodule Symbiosis

Abstract: Rhizobia are able to infect legume roots, elicit root nodules, and live therein as endosymbiotic, nitrogen-fixing bacteroids. Host recognition and specificity are the results of early programming events in bacteria and plants, in which important signal molecules play key roles. Here, we introduce a new aspect of this symbiosis: the adaptive response to hosts. This refers to late events in bacteroids in which specific genes are transcribed and translated that help the endosymbionts to meet the disparate environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
67
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 40 publications
2
67
0
Order By: Relevance
“…This led us to speculate that glycolaldehyde is oxidized to glyoxylate, which can be fed into at least two pathways: (i) reduction to glycerate through the activity of glyoxylate carboligase (blr3166) (42) and tartronate semialdehyde reductase (blr3168), or (ii) oxidation to oxalate followed by the stepwise, complete oxidation to formate and CO 2 through the activities of Oxc and Frc (43,44) and formate dehydrogenase. We previously showed that only the enzymes Oxc and Frc involved in the second pathway were detected in bacteroids during symbiosis with all different host plants (12,21) (Table 1). Interestingly, using qPCR analysis, an elevated expression of bll3157 and bll3156 was not observed in B. japonicum cultures grown in minimal medium with succinate as the carbon source.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This led us to speculate that glycolaldehyde is oxidized to glyoxylate, which can be fed into at least two pathways: (i) reduction to glycerate through the activity of glyoxylate carboligase (blr3166) (42) and tartronate semialdehyde reductase (blr3168), or (ii) oxidation to oxalate followed by the stepwise, complete oxidation to formate and CO 2 through the activities of Oxc and Frc (43,44) and formate dehydrogenase. We previously showed that only the enzymes Oxc and Frc involved in the second pathway were detected in bacteroids during symbiosis with all different host plants (12,21) (Table 1). Interestingly, using qPCR analysis, an elevated expression of bll3157 and bll3156 was not observed in B. japonicum cultures grown in minimal medium with succinate as the carbon source.…”
Section: Resultsmentioning
confidence: 99%
“…To further analyze the hypothesis that oxalate degradation is linked to arabinose utilization, a ⌬frc-oxc mutant strain was con- (12,21). The proteomics data summarize expression from three independent biological replicates.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations